Thermo-mechanical characterization of NiTi orthodontic archwires with graded actuating forces. (July 2020) - Rodrigues, P. Freitas; Fernandes, F.M. Braz; Magalhães, R.; Camacho, E.; Lopes, A.; Paula, A.S.; Basu, R.; Schell, N.
Abstract: Functionally graded NiTi orthodontic archwire was tested to assess the evolution of the actuation force as a function of the temperature. Varying actuation forces on the same orthodontic wire allow the optimization of repositioning of the different types of teeth, according its radicular support. The wire was separated into three segments: Incisive, Premolar and Molar. The functionally graded NiTi orthodontic archwire segments have distinct structural and mechanical behavior as confirmed by differential scanning calorimetry, synchrotron-based X-ray diffraction, and thermomechanical analysis. The mechanical behavior was analyzed by three-point bending tests at four different temperatures (5, 20, 25 and 37 °C). In parallel, three-point bending tests were performed by TMA analysis in a temperature range from 5 °C (from cold water) to 40 °C (hot meal). This study showed the comparison of the different segments on the same archwire, providing a better understanding of the behavior of these functionally graded materials. Graphical abstract: Image 1